The Effects of General Anaesthesia and Light on Behavioural Rhythms and GABAA Receptor Subunit Expression in the Mouse SCN. - Chong J; Cheeseman JF; Pawley MDM; Kwakowsky A; Warman GR (MDPI (Basel, Switzerland), 2021)
General anaesthesia (GA) is known to affect the circadian clock. However, the mechanisms that underlie GA-induced shifting of the clock are less well understood. Activation of γ-aminobutyric acid (GABA)-type A receptors (GABAAR) in the suprachiasmatic nucleus (SCN) can phase shift the clock and thus GABA and its receptors represent a putative pathway via which GA exerts its effect on the clock. Here, we investigated the concurrent effects of the inhalational anaesthetic, isoflurane, and light, on mouse behavioural locomotor rhythms and on α1, β3, and γ2 GABAAR subunit expression in the SCN of the mouse brain. Behavioural phase shifts elicited by exposure of mice to four hours of GA (2% isoflurane) and light (400 lux) (n = 60) were determined by recording running wheel activity rhythms in constant conditions (DD). Full phase response curves for the effects of GA + light on behavioural rhythms show that phase shifts persist in anaesthetized mice exposed to light. Daily variation was detected in all three GABAAR subunits in LD 12:12. The γ2 subunit expression was significantly increased following GA in DD (compared to light alone) at times of large behavioural phase delays. We conclude that the phase shifting effect of light on the mouse clock is not blocked by GA administration, and that γ2 may potentially be involved in the phase shifting effect of GA on the clock. Further analysis of GABAAR subunit expression in the SCN will be necessary to confirm its role.
Keywords: GABA; GABAA receptor; circadian clock; general anaesthesia; phase response curve